Application of plasma electrolytic oxidation coating on powder metallurgy Ti-6Al-4V for dental implants - Garcia-Cabezón, Cristina; Rodriguez-Mendez, María Luz; Borrás, Vicente Amigo; Raquel, Bayon; Cabello, Jose Carlos Rodriguez; Fonseca, Arturo Ibañez ; 0000-0002-2223-5041; Martin-Pedrosa, Fernando (Metals, 2020)
Ti-6Al-4V alloy obtained by powder metallurgy (PM) is a good candidate biomaterial in the manufacture of dental implants but its inherent porosity makes it have worse corrosion behavior than conventionally obtained alloys. In order to improve the corrosion and biological properties, surface modification technologies could be used. The plasma electrolytic oxidation (PEO) process is a novelty process successfully used in case of conventional titanium alloys. The present work investigates the effect of PEO treatment on PM Ti-6Al-4V alloy using two electrolytes. Both coatings show good adherence and improved corrosion behavior in artificial saliva, the PEO coatings delivers a steady growth of corrosion resistance from day one until 90 days immersion. Highest corrosion resistance was shown in case of Ca/P enrichment PEO coatings. The cytocompatibility tests indicated these coatings seem to be appropriate to improve the bone osseointegration with proper porosity index.
Publisher Copyright: © 2020 by the authors. Licensee MDPI, Basel, Switzerland.
Keywords: Biocompatibility; Coating; Corrosion; Titanium based alloys